Standardization of CBCL, TRF and YSR in a sample of 6–18 year-old Lithuanian children’s - Žukauskienė, Rita; Kajokienė, Ilona (Psichologija, 2006)
It is well accepted in child psychiatry that the study of children’s adaptive behavior and psychopathology should be based on: a) multiple informants, who have different points of view and observe different behaviors in different settings; b) standardized assessment and diagnostic procedures, which makes possible communication of the results among different practitioners in the same country and allows for generalizability across cultures; c) assessment tools with a capacity to assess a broad spectrum of psychopathology; and d) economical procedures in terms of both money and time (Roussos et al., 1999). The questionnaires constructed by Thomas Achenbach meet the above criteria and have become accepted worldwide as valuable tools.